Contract warriors - Rosen, Fred (Penguin Group, 2005)
"...Drawing on historical sources and up-to-the minute reports from Iraq and other hotspots around the globe, 'Contract Warriors' sheds light on the secret world of private military companies, the tens of billions of dollars they receive, their relationship with the international arms trade, and most important, the kind of men and women who offer their services."--Back cover.